Experiences of precarity for Māori in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Albany, New Zealand - Martin, Ahnya (Massey University, 2025)
Socioeconomic precarity and in-work poverty are associated with increased exposure to ill-health and untimely death. Presently in Aotearoa New Zealand (NZ), there are many conversations in public discourse about the precariat, or people experiencing in-work poverty, and what “they” need. There are fewer conversations with households experiencing precarity to understand the insecurities they face in relation to inadequate incomes and associated insecurities in housing, food, and leisure, and how various policies designed by more affluent groups frustrate or improve their precarious situations. Successive governments have continued to act without adequate dialogue with the precariat, with less than desirable outcomes. These outcomes are particularly stark for Māori who as a result of ongoing processes and the legacies of colonisation are overrepresented within the precariat. Understanding precarity for Māori from the perspectives of those who are directly impacted is imperative if we are to ensure policy measures are successful in preventing and alleviating in-work poverty. This thesis contributes to current Indigenous efforts to theorise the contemporary and lived experiences of precarity for Māori. I have approached precarity as a cultural and economic assemblage that can be reassembled to enhance the lives of members of the precariat. Speaking to methodological pluralism, I have employed a qualitative methodology of enhanced interviewing using mapping and photo elicitation guided by Kaupapa Māori (KM) praxis to enact this culturally centred approach that is informed by tikanga (protocols/customs) Māori. Four consecutive engagements with one Cook Island Māori and nine Māori households (40 interviews in total) informed the development of various policy initiatives to address issues of precarity. Chapter 1 serves to historicise and situate the evolution of precarity within Aotearoa NZ: particularly for Māori. Chapter 2 (Publication 1) reflects on this application of KM praxis to document and respond to the everyday experiences of households living in precarity in Aotearoa NZ. I outline the relationally ethical and community-engaged methodology informed by key cultural principles which I have employed in my research design and fieldwork. The findings inform my recommendations for policy which responds to household needs. The third chapter (Publication 2) draws on assemblage theory to document the participants’ everyday experiences of precarity and how policy initiatives emerge as key elements within the everyday lives of the precariat. The fourth chapter (Publication 3) shifts the focus to householders’ engagement in leisure as they cope with and respond agentively to situations of precarity. I document how core Māori principles and processes of whanaungatanga (cultivating positive relationships) and manaakitanga (caring for self and others) are foregrounded in household engagements in contemporary leisure practices. Overall, this thesis contributes to current Indigenous theorising of precarity by providing insights into the lived experiences of the consequences of policy efforts to alleviate the multifaceted insecurities associated with household precarity. Recommendations to inform policy settings are outlined at the final discussion chapter.
Keywords: precarity, in-work poverty, Māori, policy, leisure, qualitative, Kaupapa Māori research; Māori (New Zealand people); Social life and customs; Family; Cost and standard of living; Households; Economic aspects; New Zealand; Economic conditions; Income distribution; Tāngata whenua; Whānau; Āhuatanga ōhanga; Āhuatanga pāpori; Māori Doctoral Thesis; 440301 Family and household studies; 440712 Social policy; 451127 Ngā mātai tikanga ā-iwi o te Māori (Māori sociological studies)